Current Trends in Processes of Mergers and Acquisitions in the Global Business Environment - Potynska, Yana (Lesya Ukrainka Volyn National University, 2024)
The relevance of the research topic is determined by the fact that mergers and acquisitions are becoming more popular ways to create new businesses, and they are becoming tools that can help companies survive in fierce competition. This bachelor's thesis examines the theoretical and methodological foundations of current trends in the development of mergers and acquisitions in the global business environment. The first chapter reveals the theoretical and methodological foundations of the study of the concept of mergers and acquisitions in international business, their essence and characteristics, defines the classification of mergers and acquisitions, motives and mechanisms for their implementation, and substantiates the impact of mergers and acquisitions on the functioning of the global business environment. The second chapter analyzes the geography of M&A processes, determines the sectoral distribution and dynamics of M&A processes, and identifies the peculiarities of M&A development in Ukraine The third chapter characterizes global trends in the development of mergers and acquisitions, identifies expectations for mergers and acquisitions in the global business environment, and substantiates the prospects for the development of mergers and acquisitions in Ukraine.
Keywords: M&A transactions; mergers; acquisitions; business environment; M&A processes; global economy; global M&A market; regional structure of mergers and acquisitions